THE INFLUENCE OF CUSTOMER ENGAGEMENT, PERCEIVED EASE OF USE AND CONVENIENCE ON CUSTOMER LOYALTY AMONG SHOPEEPAY USERS WITH PERCEIVED VALUE AS A MEDIATING VARIABLE - Fransiska Amanda; Ni Made Ratih Nurmalasari (Sekolah tinggi ilmu ekonomi pemuda, 2026)
ABSTRACT The development of digital technology has led to an increase in the use of digital wallets, including ShopeePay, as a practical and efficient transaction tool. Customer loyalty is a key factor for ShopeePay to maintain its competitiveness amid increasingly fierce competition. This study aims to analyze the effect of Customer Engagement, Perceived Ease of Use, and Convenience on Customer Loyalty, with Perceived Value as a mediator variable.This research uses a quantitative approach with a survey method of ShopeePay users. The data analysis technique used is Partial Least Square-Structural Equation Modeling (PLS-SEM) to test the relationship between research variables.The results of this study are expected to provide deeper insight into the factors that influence ShopeePay customer loyalty. Practically, the results of this study can help ShopeePay in designing more effective marketing strategies, increasing customer engagement, and increasing the comfort and ease of use of their services in order to maintain customer loyalty.